Geographic and Educational Factors and Risk of the First Peritonitis Episode in Brazilian Peritoneal Dialysis Study (BRAZPD) Patients - Martin, Luis Cuadrado [UNESP]; Caramori, Jacqueline Socorro Costa Teixeira [UNESP]; Fernandes, Natalia; Divino-Filho, Jose C.; Pecoits-Filho, Roberto; Barretti, Pasqual [UNESP] (Amer Soc Nephrology, 2011)
Background and objectives Peritonitis remains as the most frequent cause of peritoneal dialysis (PD) failure, impairing patient's outcome. No large multicenter study has addressed socioeconomic, educational, and geographic issues as peritonitis risk factors in countries with a large geographic area and diverse socioeconomic conditions, such as Brazil.Design, setting, participants, & measurements Incident PD patients recruited from 114 dialysis centers and reporting to BRAZPD, a multicenter observational study, from December 2004 through October 2007 were included. Clinical, dialysis-related, demographic, and socioeconomic variables were analyzed. Patients were followed up until their first peritonitis. Cox proportional model was used to determine independent factors associated with peritonitis.Results In a cumulative follow-up of 2032 patients during 22.026 patient-months, 474 (23.3%) presented a first peritonitis episode. In contrast to earlier findings, PD modality, previous hemodialysis, diabetes, gender, age, and family income were not risk predictors. Factors independently associated with increased hazard risk were lower educational level, non-white race, region where patients live, shorter distance from dialysis center, and lower number of patients per center.Conclusions Educational level and geographic factors as well as race and center size are associated with risk for the first peritonitis, independent of socioeconomic status, PD modality, and comorbidities. Clin J Am Soc Nephrol 6: 1944-1951, 2011. doi: 10.2215/CJN.11431210